Crystallization and preliminary X‐ray characterization of the full‐length bacteriophytochrome from the plant pathogen Xanthomonas campestris pv. campestris. Issue 12 (1st December 2014) - Klinke, Sebastián; Otero, Lisandro H.; Rinaldi, Jimena; Sosa, Santiago; Guimarães, Beatriz G.; Shepard, William E.; Goldbaum, Fernando A.; Bonomi, Hernán R.
<x xml:space="preserve">Abstract</x> Phytochromes give rise to the largest photosensor family known to date. However, they are underrepresented in the Protein Data Bank. Plant, cyanobacterial, fungal and bacterial phytochromes share a canonical architecture consisting of an N‐terminal photosensory module (PAS2–GAF–PHY domains) and a C‐terminal variable output module. The bacterium Xanthomonas campestris pv. campestris, a worldwide agricultural pathogen, codes for a single bacteriophytochrome (XccBphP) that has this canonical architecture, bearing a C‐terminal PAS9 domain as the output module. Full‐length XccBphP was cloned, expressed and purified to homogeneity by nickel–NTA affinity and size‐exclusion chromatography and was then crystallized at room temperature bound to its cofactor biliverdin. A complete native X‐ray diffraction data set was collected to a maximum resolution of 3.25 Å. The crystals belonged to space group P43212, with unit‐cell parameters a = b = 103.94, c = 344.57 Å and a dimer in the asymmetric unit. Refinement is underway after solving the structure by molecular replacement.